2019
DOI: 10.1111/cpr.12735
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potentials and modulatory mechanisms of fatty acids in bone

Abstract: Bone metabolism is a lifelong process that includes bone formation and resorption. Osteoblasts and osteoclasts are the predominant cell types associated with bone metabolism, which is facilitated by other cells such as bone marrow mesenchymal stem cells (BMMSCs), osteocytes and chondrocytes. As an important component in our daily diet, fatty acids are mainly categorized as long‐chain fatty acids including polyunsaturated fatty acids (LCPUFAs), monounsaturated fatty acids (LCMUFAs), saturated fatty acids (LCSFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 299 publications
(627 reference statements)
5
78
0
Order By: Relevance
“…The n-3 fatty acids EPA and DHA are suggested to stimulate osteoblast survival, promote osteoblastogenesis, and prevent bone resorption by altering membrane function, regulating calcium balance, and enhancing osteoblast activity [ 36 ]. Furthermore, the involvement of EPA and DHA in preosteoblast differentiation and maturation was associated with their anti-inflammatory effects, i.e., reducing the synthesis of inflammatory PGE2 and modulating peroxisome proliferators-activated receptor gamma (PPARgamma) and lower levels of inflammatory cytokines, e.g., interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) [ 36 ]. Regarding bone health, a recent meta-analysis on observational studies noticed that a higher dietary intake of n-3 fatty acids was significantly associated with a lower risk of hip fracture [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The n-3 fatty acids EPA and DHA are suggested to stimulate osteoblast survival, promote osteoblastogenesis, and prevent bone resorption by altering membrane function, regulating calcium balance, and enhancing osteoblast activity [ 36 ]. Furthermore, the involvement of EPA and DHA in preosteoblast differentiation and maturation was associated with their anti-inflammatory effects, i.e., reducing the synthesis of inflammatory PGE2 and modulating peroxisome proliferators-activated receptor gamma (PPARgamma) and lower levels of inflammatory cytokines, e.g., interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) [ 36 ]. Regarding bone health, a recent meta-analysis on observational studies noticed that a higher dietary intake of n-3 fatty acids was significantly associated with a lower risk of hip fracture [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that RvE1 is effective in preventing and restoring bone loss in periodontitis [ 62 , 63 ]. Additionally, polyunsaturated fatty acids (PUFAs), such as omega-3, exert osteoprotective functions (promoting the differentiation and activation of osteoblasts), while inhibiting osteoclast activities [ 64 ]. Indeed, a very recent study reported that adjunctive omega-3 and low-dose aspirin provided clinical and immunological benefits to the treatment of periodontitis in patients with type 2 diabetes after periodontal debridement [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fas are further categorized as long-chain fatty acids, which include polyunsaturated fatty acids (LCPUFAs), monounsaturated fatty acids (LCMUFAs), saturated fatty acids (LCSFAs), medium-/short-chain fatty acids (MCFAs/SCFAs) as well as their metabolites. These Fas are closely associated with bone health as well as bone disorders [ 71 ].…”
Section: Function Of Fatty Acid In Osteoclastsmentioning
confidence: 99%